PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DALAM PENINGKATAN KETERAMPILAN MENYELESAIKAN SOAL CERITA PADA PEMBELAJARAN MATEMATIKA KELAS V SD1) - Lestari, Umi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The use of cooperative learning model type NHT to improve the ability in solving story problem at mathematics learning of the fifth grade students of SD N Pesalakan. The objective of this research is to improve the ability in solving story problem at mathematics learning of the fifth grade students of elementary school. This research was conducted through two cycles. The subject of this research is all fifth grade students of SD Negeri Pesalakan that consists of 23 students. The source of the data of this research is students, teachers, and documentation. Technique of collecting data used observation, documentation, and test. Validity of the data used triangulation of method and source. Technique of data analysis of this research used qualitative and quantitative method. Based on the result of the research, it can be concluded that the use of cooperative learning model type |NHT can improve the ability in solving story problem at mathematics learning in the fifth class if the steps of using NHT is practiced appropriately. Key words: NHT Model, Story Problem, Mathematics Learning Abstrak: Penggunaan Model Pembelajaran Kooperatif Tipe NHT dalam Peningkatan Keterampilan Menyelesaikan Soal Cerita pada Pembelajaran Matematika Kelas V SD. Penelitian ini bertujuan untuk meningkatkan keterampilan menyelesaikan soal cerita pada pembelajaran Matematika siswa kelas V SD. Penelitian ini dilaksanakan dalam dua siklus. Subjek penelitian ini adalah seluruh siswa kelas V SD Negeri Pesalakan yang berjumlah 23 siswa. Sumber data dalam penelitian ini adalah siswa, teman sejawat, dan dokumen. Teknik pengumpullan data menggunakan observasi, dokumentasi, dan tes. Validitas data menggunakan teknik triangulasi metode dan sumber. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Berdasarkan hasil penelitian, dapat disimpulkan bahwa penggunaan model pe.belajaran kooperatif tipe NHT dapat meningkatkan keterampilan menyelesaikan soal cerita pada pembelajaran Matematika di kelas V SD apabila dilaksanakan sesuai langkah-langkah yang tepat . Kata Kunci: Model NHT, Soal Cerita, Pembelajaran Matematika